SOCIAL AWARENESS IN PRAMOEDYA ANANTA TOER’S NOVEL THIS EARTH OF MANKIND - Nadila, Nurul; Sahri, Zulfan (Universitas Islam Sumatera Utara, 2025)
This study examines the representation of social awareness in Pramoedya Ananta Toer’s novel This Earth of Mankind, using Sheldon’s framework. Through qualitative descriptive analysis, the study identifies three dimensions of social awareness—cognition, social environment, and goals and motives—reflected in the characters of Minke, Nyai Ontosoroh, and Tuan de la Croix. The findings highlight Pramoedya’s critique of colonial social hierarchies and the awakening of native consciousness. Twelve data were collected to support the statement about social awareness and its aspects found in the novel. The results of this study are that there are three aspects of social awareness found in the novel This Earth of Humanity, namely cognition, social environment, and goals and motives. The cognition can be seen through Minke’s character, which is displayed through his disbelief in Astrology and superstition, his good process of absorbing information, and his way of thinking critically about the problems of the indigenous people. The social environment can be seen through social awareness of the backwardness of natives’ behavior and social awareness of native status towards Europeans. Goals and motives can be seen through the goals of Minke and Tuan de la Croix, who wanted to make the natives more advanced and developed, and Nyai Ontosoroh's goals for Annelies.